PELAYANAN PEMBELAJARAN DI SEKOLAH MENENGAH NEGERI ATAS 1 GAMPING, KABUPATEN SLEMAN, PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Naina Aqmarina, Putri; Suwardi, Suwardi; Suryo, Herning (Master of Public Administration, Universitas Slamet Riyadi, 2024)
This study to analyse and describe learning services at SMA Negeri 1 Gamping from the perspective of service quality and to analyse and describe learning services at SMA Negeri 1 Gamping from the perspective of service performance. This type of research is a mix method, where the results of quantitative research on service quality using questionnaires as a data collection tool are compared with the results of qualitative research on service performance using interview techniques. The sample in quantitative research amounted to 100 XI grade students consisting of 4 study groups with random sampling and interviews with teachers, administration, and waka sarpras as supporting data in qualitative research. The results showed that learning services at SMA N 1 Gamping from the perspective of service quality received an average score of 3.45 with quality categories, and learning services at SMA N 1 Gamping from the perspective of service performance refer to the accreditation results issued by the National Accreditation Board for Schools/Madrasah Number 974/BAN-SM/SK/2019 dated 5 November 2019 with the accreditation predicate A (Superior). It can be concluded that the A (Superior) accreditation predicate in the aspect of service performance only gets the Quality category in service quality and has not reached the High quality category